KOMUNIKASI TERAPEUTIK PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA BUDI LUHUR JAMBI - Faridah Faridah; Iin Indrawati (Jurnal Abdimas Kesehatan (JAK), 2019)
Communication is a basic element of human interaction that allows one to establish, maintain and improve contracts with others because communication is done by someone, every day people often mistakenly think that communication is easy. But actually it is a complex process that involves behavior and relationships and allows individuals to associate with others and with their surroundings.As an effort to improve elderly health, it is necessary to continuously provide information to scientists, both individuals and groups so that the elderly can change from not knowing to knowing that the elderly can live healthy and productive lives, but with limited physical, psychological and mental needs approaches and methods so that messages are delivered more effectively.The method carried out on the elderly in providing information about the Healthy Lifestyle for the Elderly and the importance of eating fruit and vegetables through the approach of "therapeutic communication in the elderly". This activity was held on December  2018.The results are elements of a conducive situation, knowledge of the elderly, elderly attitudes towards the implementation of counseling, messages conveyed verbally and written after counseling with the therapeutic communication approach of the elderly, easier to understand the counseling material provided.The reduced understanding of the elderly in receiving information provided by the PSTW or the community is due to the reduced ability to listen to the elderly in providing counseling to improve the counseling method for the elderly so as not to be monotonous, so that the elderly easily understand the health information provided